The readability 'Sangkuriang': asal-mula tangkuban perahu' folklore for elementary school students using gunning fog index - Welsi Damayanti; Jendriadi; Ida Nuraeni; Abdul Razak (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Folklore in Indonesia is widely available in written form on various social media platforms. One of them is included in a PDF book entitled '30 Indonesian folklore about the Origin of the Naming of a Region in Indonesia. The first folklore in the book is entitled 'Sangkuriang: Asal-Mula Tangkuban Perahu.' This folklore has the potential to be taught in elementary schools. Therefore, a study of its readability is needed. This study aims to describe the readability of the 'Sangkuriang: Asal-Mula Tangkuban Perahu' folklore being read by elementary school students. Library research was conducted in the 2024/2025 academic year. Data on the readability of the 'Sangkuriang: Asal-MulaTangkuban Perahu' folklore were analyzed using the gunning fog index. The research results indicate that the folklore 'Sangkuriang: Asal-Mula Tangkuban Perahu' has a range of values, with the highest value of 6.60 found in paragraph 6 and the lowest value of 3.13 in paragraph 12. This number falls within the category <7.00, which corresponds to the elementary school level, indicating that the folktale is suitable for high school students to read. The implementation involves the compilers of Indonesian language textbooks in high school using this folktale text for its literary aspect.